CONSTRUCTION ACCOUNTABILITY KWANGKAY - Fibriyani Nur Khairin; Anjani Risa Pratiwi; syah, sultan (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
This study aims to construct the form of practice and the meaning of accountability in traditional ceremonies. The study population was the Dayak tribe and the study sample was the Daya Banuaq Tribe who performed the kwangkay ceremony. This research uses qualitative methods with a case study approach on the Continent Dayak Tribe in East Kalimantan. The data collection technique uses the snowball method during 2020-2022. Data sources are obtained through observation, interviews, documents, and audio visuals. The results showed that through the traditional kwangkay ceremony there was a practice of returning favors to those who had died. The Kwangkay ceremony costs a lot so it must be held accountable both individually (between families) and groups of people (community). This form of accountability is needed to increase trust and acceptance between family and community which is divided into two dimensions, namely; spiritual accountability and physical accountability. This accountability prioritizes the principles of good governance as important findings in the implementation of this ceremony, including participation, transparency and responsiveness. This research contributes to the theory of action by involving aspects of cultural identity, symbolism, social solidarity, and behavioral regulation. Contributing to practice, the Kwangkay ceremony has an important role in maintaining the cultural heritage of the Dayak tribe, strengthening social ties, and contributing to the local economy.